Differences in Muscle Metabolism Between Triathletes and Normally Active Volunteers Investigated Using Multinuclear Magnetic Resonance Spectroscopy at 7T - Klepochová, Radka; Valkovič, Ladislav; Hochwartner, Thomas; Triska, Christoph; Bachl, Norbert; Tschan, Harald; Trattnig, Siegfried; Krebs, Michael; Krššák, Martin (Frontiers in Physiology, 2018)
Purpose: The influence of endurance training on skeletal muscle metabolism can currently be studied only by invasive sampling or through a few related parameters that are investigated by either proton (1H) or phosphorus (31P) magnetic resonance spectroscopy (MRS). The aim of this study was to compare the metabolic differences between endurance-trained triathletes and healthy volunteers using multi-parametric data acquired by both, 31P- and 1H-MRS, at ultra-high field (7T) in a single experimental protocol. This study also aimed to determine the interrelations between these MRS-derived metabolic parameters. Methods: Thirteen male triathletes and ten active male volunteers participated in the study. Proton MRS data from the vastus lateralis yielded concentrations of acetylcarnitine, carnosine, and intramyocellular lipids (IMCL). For the measurement of phosphodiesters (PDEs), inorganic phosphate (Pi), phosphocreatine (PCr), and maximal oxidative capacity (Qmax) phosphorus MRS data were acquired at rest, during six minutes of submaximal exercise and following immediate recovery. Results: The triathletes exhibited significantly higher IMCL levels, higher initial rate of PCr resynthesis (VPCr) during the recovery period, a shorter PCr recovery time constant (τPCr), and higher Qmax. Multivariate stepwise regression analysis identified PDE as the strongest independent predictor of whole-body maximal oxygen uptake (VO2max). Conclusion: In conclusion, we cannot suggest a single MRS-based parameter as an exclusive biomarker of muscular fitness and training status. There is, rather, a combination of different parameters, assessable during a single multi-nuclear MRS session that could be useful for further cross-sectional and/or focused interventional studies on skeletal muscle fitness and training effects.